2004
DOI: 10.1158/0008-5472.can-04-1178
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic Acid Induces Neuroblastoma Cell Death by Inhibiting Proteasomal Degradation of Retinoic Acid Receptor α

Abstract: To seek a novel therapeutic approach to neuroblastoma (NBL), we used three NBL cell lines (SK-N-DZ, NH12, and SK-N-SH) to examine the underlining molecular mechanisms of cellular reactions and sensitivity to all-trans-retinoic acid (ATRA). SK-N-DZ cells expressed relatively high levels of retinoic acid receptor ␣ (RAR-␣) and underwent ATRA-induced cell death that was blocked by an RAR-␣ antagonist. By contrast, RAR-␣ expression gradually decreased in NH12 and SK-N-SH cells, which did not experience increased c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
19
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 24 publications
6
19
0
1
Order By: Relevance
“…Intriguingly, in the ST1926-resistant subline, ATRA treatment enhanced the expression of both RARa and total RARb, with early accumulation in G2 phase. This modulation of RARs' expression was consistent with reported lines of evidence showing a correlation between RA sensitivity and inhibition of RARa-catabolism, amplification of RARa-transcription (Nagai et al, 2004) and to increased expression of RARb in NB cells (Perez-Juste and Aranda, 1999). Furthermore, there are reported lines of evidence that inhibition of proteasome by MG132 enhances ATRA responsivity (Nagai et al, 2004).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Intriguingly, in the ST1926-resistant subline, ATRA treatment enhanced the expression of both RARa and total RARb, with early accumulation in G2 phase. This modulation of RARs' expression was consistent with reported lines of evidence showing a correlation between RA sensitivity and inhibition of RARa-catabolism, amplification of RARa-transcription (Nagai et al, 2004) and to increased expression of RARb in NB cells (Perez-Juste and Aranda, 1999). Furthermore, there are reported lines of evidence that inhibition of proteasome by MG132 enhances ATRA responsivity (Nagai et al, 2004).…”
Section: Discussionsupporting
confidence: 90%
“…5B). Proteasome inhibition by MG132 was reported to enhance the cellular responsivity to ATRA (Nagai et al, 2004). Therefore, we explored a possible role for the proteasome in our model of ATRA-sensitivity shown by the retinoid resistant subline.…”
Section: Roles Of Ceramide Generation and Proteasome On Atra-mediatedmentioning
confidence: 99%
“…All-trans-retinoic acid activates phosphatidylinositol 3 0 -kinase-Akt pathway that plays an important role in neuronal differentiation (Encinas et al, 1999;Lopez-Carballo et al, 2002), and it reduces the expression levels of MYCN (Thiele et al, 1985) and upregulates the cyclin-dependent kinase (CDK) inhibitor p27 KIP1 in association with the ATRA-induced cell cycle arrest in neuroblastoma cells (Lee et al, 1996;Nakamura et al, 2003). In addition, certain neuroblastoma cells underwent apoptosis in response to ATRA (Piacentini et al, 1992;Takada et al, 2001;Nagai et al, 2004). Consistent with these observations, 13-cis-RA treatment after intensive chemotherapy improved an event-free survival rate of the patients with aggressive neuroblastomas with 17% increase (Villablanca et al, 1995;Matthay et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that the effect of RA, in terms of inducing or inhibiting degradation of RARa, is cell type specific (30)(31)(32). We observed that ATRA caused a decrease in RARa levels in the cultured neurons, and this decrease was not altered by p38 MAPK inhibition.…”
Section: Discussionmentioning
confidence: 47%